The effectiveness of laparoscopic choledochoduodenostomy for management of persistent common bile duct stones and advanced malignant obstructive jaundice - Grubnik, V. V.; Grubnik, Y. V.; Ilyashenko, V. V.; Grubnik, M. Y.; Grubnyk, V. V. (General Surgery, 2025)
Endoscopic clearance of common bile duct (CBD) stones and stenting for distal biliary obstruction are standard treatments, but can fail in cases of large calculi or advanced malignancy. Laparoscopic choledochoduodenostomy (LCCD) offers an internal bypass of the obstructed bile duct. Objective – to evaluate the safety and effectiveness of LCCD in patients with persistent CBD stones after failed endoscopic clearance and in those with advanced malignant obstructive jaundice. Materials and methods. We reviewed 55 patients who underwent LCCD at our center between 2018 and 2024. Of these, 26 patients had large CBD stones not cleared by endoscopic retrograde cholangiopancreatography, and 29 had unresectable distal malignant obstruction (pancreatic or ampullary carcinoma). All procedures were performed laparoscopically using five trocars, with a longitudinal choledochotomy and duodenotomy, a side‑to‑side biliary–enteric anastomosis hand‑sewn with absorbable barbed sutures (V‑Loc™ 3‑0), and concurrent cholecystectomy. Perioperative outcomes, complications, and follow‑up results were analyzed. Results. LCCD was completed successfully in all 55 patients with no conversions to open surgery. The mean operative time was 76 minutes (range: 55 – 110 minutes). There were no major postoperative complications or 30‑day mortality. The average hospital stay was 5.2±2.1 days. Stone patients had 92% clearance of CBD stones with no residual obstruction or recurrent cholangitis observed over a follow‑up of up to 5 years. In the malignant group, jaundice was effectively palliated in all cases, with no patient requiring repeat biliary bypass surgery during their remaining life span. Conclusions. Laparoscopic choledochoduodenostomy proved to be a safe and effective procedure for both complex CBD stones after failed endoscopic retrograde cholangiopancreatography and for palliative relief of malignant obstructive jaundice. The technique achieved durable biliary drainage with minimal morbidity and short hospital stay. LCCD should be considered as an alternative when endoscopic management is unsuccessful or not feasible, offering definitive resolution of CBD stones and excellent palliative outcomes in advanced malignancies.